THE EFFECT OF WORDWALL ON STUDENTS LEARNING MOTIVATION AT SMP NEGERI 1 KUALA BATEE - Roshi, Hiyana; isna, nuzulul isna (English Education Department at FKIP Nommensen University, 2025)
This study aims to explore the effect of using Wordwall on student learning motivation at SMP Negeri 1 Kuala Batee. To find out how the effect of using Wordwall interactive learning media on the learning motivation of seventh grade students. This research was conducted at SMP Negeri 1 Kuala Batee, this type of research is quantitative descriptive research, the subject of this research is class VII students totaling 90 people, the sampling method uses random sampling, this research uses a survey in which the data collection is done through a questionnaire, which is a learning interest data instrument measured using a Likert scale, the data in this study were processed using statistical analysis procedures using IBM SPSS Statistic (version 27.0.1). The findings of this study resulted in a Mann-Whitney U value of U 000, with p < 0.001 (two-tailed). This result indicates a statistically significant difference in motivation levels between the two groups. Further research results regarding student inte1`rest can be discussed in this journal